Diagnosis of Rare Association of Orthotopic Multicystic Dysplasia with Crossed Fused Renal Ectopia. (15th April 2014) - Tang, Linnan; Koshy, June; Spevak, Melissa R.; Benson, Jane E.; Bosemani, Thangamadhan
Abstract : Orthotopic multicystic dysplastic kidney with crossed fused ectopia is a rare congenital anomaly. This congenital anomaly may give an appearance of a solitary kidney morphology during the initial imaging evaluation. A solitary kidney should be carefully evaluated for the presence of duplication, horseshoe configuration, or crossed renal ectopy. Vesicoureteral reflux is a common finding associated with a multicystic dysplastic kidney. We present an infant with an orthotopic multicystic dysplastic kidney and an inferiorly placed crossed fused ectopic kidney. The presence of a complex congenital anomaly may warrant further evaluation with cross-sectional imaging to depict the anatomy and structure.